Reactivity of β-enamino ester of benzo[f]chromene: One pot synthesis of isolated and heterocycle-fused derivatives of benzo[f] chromene - El-Rady, Eman Abd; El-Azab, Islam Helmy (European Journal of Chemistry, 2012)
The formation of isolated and fused benzo[f]chromene derivatives was achieved via reacting ethyl 3-amino-1-phenyl-1H-benzo[f]chromene-2-carboxylate (1) with some selected reagents under basic conditions. The new compound, ethyl 3-(dimethylaminomethyleneamino)-1-phenyl-1H-benzo[f]chromene-2-carboxylate (2) was prepared from compound 1 and N,N-dimethyl formamide in presence of phosphorus oxychloride under mild conditions in excellent yield using Vilsmeier reaction. Also, 10-amino-12-phenyl-9-sulfanyl-12H-benzo[f] chromeno[2,3-d]pyrimidine-11(10H)-one (12), 10-aryl-14-phenyl-14H-benzo[f]chromeno [2,3-d][1,3,4]thiadiazolo[3,2-a]pyrimidine-13-one (15), ethyl 3-(4-oxo-2-thioxothiazolidin-3-yl)-1-phenyl-1H-benzo[f]chromene-2-carboxylate (18), ethyl 3-(4-phenyl-2-thioxothiazol-3(2H)-yl)-1-phenyl-1H-benzo[f]chromene-2-carboxylate (20), ethyl 3-acetamido-1-phenyl-1H-benzo[f]chromene-2-carboxylate (21), and 10-amino-9-methyl-12-phenyl-12H-benzo[f] chromeno[2,3-d]pyrimidine-11(10H)-one (23) were prepared. The structures of these compounds were established by elemental analysis, IR, MS and NMR spectral analysis.